2013
DOI: 10.1037/a0033287
|View full text |Cite
|
Sign up to set email alerts
|

Intentionally forgetting other-race faces: Costs and benefits?

Abstract: Eyewitnesses to events with multiple actors might be aware that during a subsequent investigation some actors will need to be remembered and others can be forgotten. Research on the directed-forgetting procedure suggests that when some information is cued to be forgotten, retention of other information is enhanced. In three experiments, directed-forgetting conditions were compared with control conditions to assess potential costs and benefits of forgetting other-race faces. In Experiment 1, undergraduate stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…A significant DF effect was obtained for own-race faces, revealing better memory for items cued to remember compared to items cued to forget. This finding is in line with previous work (Fitzgerald et al, 2013;Goernert et al, 2011;Metzger, 2011;Paller et al, 1999) demonstrating that memory for faces can be intentionally modulated. Importantly, the DF effect was further found to depend on the ethnicity of the faces, as it was absent for otherrace faces.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…A significant DF effect was obtained for own-race faces, revealing better memory for items cued to remember compared to items cued to forget. This finding is in line with previous work (Fitzgerald et al, 2013;Goernert et al, 2011;Metzger, 2011;Paller et al, 1999) demonstrating that memory for faces can be intentionally modulated. Importantly, the DF effect was further found to depend on the ethnicity of the faces, as it was absent for otherrace faces.…”
Section: Discussionsupporting
confidence: 93%
“…So far, only very few studies have investigated DF using faces. A DF effect is typically reported in these studies (Fitzgerald, Price, & Oriet, 2013;Goernert, Corenblum, & Otani, 2011;Metzger, 2011;Paller et al, 1999; but see Reber et al, 2002), suggesting that memory for faces is to some extent susceptible to intentional forgetting.…”
Section: Intentionally Remembering or Forgetting Own-and Other-race Fmentioning
confidence: 69%
See 1 more Smart Citation
“…The focus of the current study is on the racial identity of the faces, and its potential interaction with DF. Fitzgerald et al ( 2013 ) manipulated racial attributes of studied faces and found the magnitude of the DF effect to differ between Asian and Black faces. However, since only the other-race faces were presented and tested (i.e., no Caucasian faces were presented in the study, whereas the participants were Caucasian), direct comparison between DF of own- and other-race faces could not be assessed.…”
Section: Introductionmentioning
confidence: 99%